2015
DOI: 10.1111/anec.12331
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intraventricular Conduction Disturbances in a Large French Population

Abstract: Our results are comparable to studies concerning low cardiovascular risks populations. The association between ICoD and cardiovascular diseases needs to be studied in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 11 publications
2
10
4
Order By: Relevance
“…Intraventricular conduction disturbances were found in one out of 20 participants (5.1%), a value in mid-range of other studies (3.1% and 9.6%) [10,23] and similar to the one found by Rasmussen et al (4.4%) [3]. Those variations may be due to the definitions of intraventricular conduction disturbances subtypes used or to the characteristics of the samples studied [e.g.…”
Section: Prevalence Of Intraventricular Conduction Disturbancessupporting
confidence: 79%
See 1 more Smart Citation
“…Intraventricular conduction disturbances were found in one out of 20 participants (5.1%), a value in mid-range of other studies (3.1% and 9.6%) [10,23] and similar to the one found by Rasmussen et al (4.4%) [3]. Those variations may be due to the definitions of intraventricular conduction disturbances subtypes used or to the characteristics of the samples studied [e.g.…”
Section: Prevalence Of Intraventricular Conduction Disturbancessupporting
confidence: 79%
“…Those variations may be due to the definitions of intraventricular conduction disturbances subtypes used or to the characteristics of the samples studied [e.g. the study by Monin et al was based on a young and healthy population [23]].…”
Section: Prevalence Of Intraventricular Conduction Disturbancesmentioning
confidence: 99%
“…The second more frequent major ECG abnormalities was ventricular conduction defect (complete or intermittent intraventricular blocks) and were more frequent in women, but with no statistically significant difference (0.56% vs 1.06%; p = 0.208). A study carried out in Latinos and Polish found similar findings [17] , [38] , while studies in South Africans, middle-aged Africans, French and Americans found different results [10] , [13] , [18] , [39] . The ventricular conduction defect in this sample can be explained by the higher proportion of individuals with hypertension as this condition is known to be harmful for the ventricular conduction system [3] , [4] , [40] , [41] .…”
Section: Discussionmentioning
confidence: 87%
“…In the general population, the rate of bundle branch blocks is lower and more frequent is the right bundle branch block [17]. In the case of syncope in a patient with a left bundle branch block, it is likely that the syncope may result from the paroxysmal atrioventricular block [18].…”
Section: Discussionmentioning
confidence: 99%